Analysis Of Liquidity Ratio, Solvency, Activity And Profitability In Assessing Financial Performance At Pt. Indofood Cbp Success Makmur Tbk - Riyan Irawan; Enjang Suherman; Dwi Epty Hidayati (International Journal of Applied Finance and Business Studies, 2022)
This study aims to determine the company's financial performance using financial ratio analysis. The financial ratios used are the ratios of liquidity, solvency, activity and profitability. The data analysis method used is descriptive analysis using quantitative data calculations in the form of financial statements. Based on the results of the overall liquidity ratio, the company's state is in good condition. Based on the sovability ratio in PT. Indofood CBP Sukses Makmur Tbk in 2016-2019 was declared in good condition because it was considered capable of meeting its long-term debt. For solvency ratios in PT. Indofood CBP Sukses Makmur Tbk in 2020-2021 was declared in a bad state because it could not meet its long-term debt. Based on the ratio of Activity as measured by receivable turn over, Fixed Asset Turn Over, Inventory Turn Over in PT. Indofood CBP Sukses Makmur Tbk in 2016-2021 was declared in good condition. However, the ratio measured by total assets turn over is considered less than optimal because in 2020-2021 there has been an increase in total assets. Based on profitability asio at PT. Indofood CBP Sukses Makmur Tbk in 2016-2021 was declared in a bad state. PT. Indofood CBP Sukses Makmur Tbk, must be able to manage its assets properly in order to be able to generate maximum profit from sales. PT. Indofood CBP Sukses Makmur Tbk, must be able to manage the company's assets and capital to increase sales so that the profits generated exceed the assets and capital owned.